Outcomes of fertility treatment in patients with cardiac disease: a multi-centre experience. (14th October 2021) - Joy, E; Skorupskaite, K; Balen, A; Cauldwell, M; Agarwal, K; English, K
Abstract: Introduction: Risks of pregnancy in women with cardiac disease are well described, but data regarding the risks of assisted conception in this cohort is limited. As increasing numbers of older women seek fertility treatment, more women with congenital heart disease desire to have children of their own, and pre-implantation genetic testing (PGT) becomes more widely adopted, increasing numbers of women at risk of cardiac complications are likely to undergo fertility treatment. Aims: To assess safety of fertility treatment in women with cardiac disease. Methods: Multi-centre retrospective review of outcomes and complications in women with cardiac disease undergoing fertility treatment. Results: 34 women with cardiac disease who underwent fertility treatment were identified, with 50 cycles undertaken. 24 patients (71%) received pre-pregnancy counselling. Four patients underwent assisted conception with PGT and two patients underwent IVF and egg collection for the purposes of surrogacy (both mWHO class III). The mean age at the start of an assisted conception cycle was 32 years. Cardiac disease was identified pre-pregnancy in 31 patients. Those diagnosed during pregnancy included a restrictive cardiomyopathy (presumed long standing), and pulmonary stenosis (PS) with an atrial septal defect (ASD). The Modified WHO (mWHO) risk category for the 34 women is seen in table 1. Those in mWHO class III include patients with mechanical valves, Fontan circulation, moderate LV systolic impairment, cyanotic heart disease due to previously undiagnosed PS and ASD, and a patient with Eisenmengers syndrome seeking surrogacy using her own eggs. Live births: 50 cycles resulted in 31 pregnancies; There were 31 live births, (including two sets of twins). One pregnancy lost a twin, and there were two first trimester miscarriages. Complications: Eight patients developed complications; four during fertility treatment and four during pregnancy (table 2). There was a correlation between higher mWHO class and higher rates of complications. No patients in mWHO class I experienced complications compared to 43% of mWHO class III. Of the 31 live births, five babies were delivered pre-term (<37/40). Conclusion: The potential cardiac risks of assisted conception in patients with known cardiac disease, or older patients with risk factors for acquired cardiac disease should be considered by both reproductive medicine specialists and cardiologists before treatment commences. Formal pre-treatment / pre-pregnancy counselling is of paramount importance and should involve dialogue between both specialties and the patient to ensure all are aware of the potential risks, and action can be taken to minimise these. However, the presence of cardiac disease per se should not necessarily prevent patients accessing fertility treatment, as in many cases it can be used safely and successfully. Funding Acknowledgement: Type of funding sources: None.